STAD Learning Using an NLP Approach Improves Indonesian Language Learning Outcomes of Elementary School Students in Lower Grades - Patni, Ni Nyoman Ayu Dhyana Radha; Maria Goreti Rini Kristiantari; Basilius Redan Werang (Universitas Pendidikan Ganesha, 2025)
The Indonesian language learning outcomes of elementary school students remain low due to the use of conventional teaching methods that fail to actively engage students. This study aims to analyze the effect of the Student Teams-Achievement Divisions (STAD) cooperative learning model based on Neuro-Linguistic Programming (NLP) in improving the Indonesian language learning outcomes of third-grade elementary school students. This research employs a quasi-experimental design with a Non-equivalent Pretest-Posttest Control Group Design. The sample consists of 48 students, divided into two groups: the experimental class, which was taught using the STAD model with NLP, and the control class, which was taught using conventional methods. Data were collected through multiple-choice objective tests and analyzed using descriptive statistics and t-tests to measure differences in learning outcomes between the groups. The results indicate a significant difference between the experimental and control groups (tcount = 5.11 > ttable = 2.00), with achievement percentages of 87% for the experimental class and 51% for the control class. These findings suggest that integrating the STAD model with NLP effectively enhances students' comprehension and learning motivation. The implications of this study highlight the importance of implementing innovative teaching strategies that accommodate students' cognitive and psychological aspects to improve the effectiveness of Indonesian language learning in elementary schools.